Effect of Conductive Baffles on Natural Convection Heat Transfer - Ali, Raed Ahmed (Nahrain University College of Engineering Journal, 2010)
Two dimensional numerical study of the effect of high thermal conductive baffles on natural convectionheat transfer in saturated porous medium inside enclosure. The top and bottom surface of the enclosure areinsulated, the two vertical walls of the enclosure have different constant temperature, high conductive thinbaffles are attached on the two vertical walls. The governing equations were solved by finite difference method.The results inserted for different value of Rayleigh number and different position s of the baffles with change inlength of baffles, when the baffles attached to the hot and cold walls in distances (0.25,0.75) respectively frombottom surface, also when the baffles attached to the hot and cold walls in distance ( 0.75 , 0.25 ) respectivelyfrom bottom surface. The length of baffles in the two cases changed in range ( 0.2 0.8 ). For the above casesThe Rayleigh number changed in range ( 150 750 ). The results are represented by streamlines and isothermlines to show the behavior of the fluid circulation and temperature distribution. Also some graphics had beenobtained which represent the relationship between Nusselt and Rayleigh numbers with the position and length ofbaffles. The results show that increasing Rayleigh number leads to increase in the Nusselt number for twocases. But in the two cases the increasing in the baffles length results a decreases in Nusselt number.(Key words: natural convection, porous medium, Baffle, Enclosure)